Match-play running demands in a female soccer professional club: From academy to professional team - Casamichana, D.; Barba, E.; Gantois, P.; Nakamura, F.; Erkizia, B.; Castellano, J. (International Journal of Sports Science & Coaching, 2024)
The objective of the study was to examine the match-running load of female soccer players competing at distinct age groups (U15, U18 and senior cohorts) belonging to the same professional club, over a competitive season. The external load variables of the official matches were monitored with Global Positioning System (GPS) technology: total distance (TD), at >18 km·h-1 (running), at >21 km·h-1 (high-speed running, HSR) and at >24 km·h-1 (sprint, SPR) distances, efforts at >85% of the maximal sprint speed (>85% MSS), acceleration load (aLoaD), accelerations (ACC2 and ACC3, >2 and >3 m·s-2) and decelerations (DEC2 and DEC3 <-2 and <-3 m·s-2). Overall, distances covered at running, HSR and sprinting were greater for senior players than their younger peers (U15 and U18; p < 0.05). Regarding HSR and sprints, no difference was found for sprints accumulated by central defender (CD) players in comparison to U18 and U15 (p > 0.05). In addition, U18 and senior players engaged more often in ACC and DEC, >2 and >3 m·s-2, respectively, than U15 players (p < 0.05). In conclusion, older female soccer players are exposed to higher match load than their younger peers. These findings could be useful for soccer coaches to design specific speed development programmes across the long-term athletic development pathway.